A Study of The Relevance of The Concepts of Taxes in Islam (Abu Yusuf's Philosophy Perspective) - Suud , Ahmad; Putri , Diana; Tjaraka , Heru (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This study aims to examine the relevance of the concept of tax in Islam according to the perspective of Abu Yusuf's philosophy. Research data was collected and analyzed using library research techniques. The findings of this study are that the concept of tax in Islam initiated by the philosopher Abu Yusuf in Kitab Al-Kharaj is still relevant to the current taxation system. Among its relevance are taxes (kharaj) collected proportionally, the idea of ​​collecting taxes by recruiting tax officials with integrity and professionalism, there is a dispute between the principles of tax collection in Islam according to the philosophy of Abu Yusuf and the principles of taxation applied in Indonesia such as the principle of imposition of principles and minimum principles which can be justified juridically, then finally between the tax (kharaj) and the Building Land Tax (PBB) there is an agreement that the object is in the form of land which is the property right. This research is expected to make a contribution both theoretically, namely related to the concept of tax in Islam, according to the perspective of Abu Yusuf's philosophy and practically for regulators (government) in formulating policies in the field of taxation so that they are more just and beneficial to the state and the people.